Poststroke depression: prevalence, pathogenesis, diagnosis, and treatment - Vladimir Anatolyevich Parfenov (Неврология, нейропсихиатрия, психосоматика, 2012)
The paper reviews the data available in the literature on the prevalence, pathogenesis, diagnosis, treatment, and prevention of poststroke depression. Depression develops in nearly one in every three patients, who have experienced stroke, and can negatively affect the rehabilitation process. The role of psychological factors, genetic predisposition, brain lesion location, monoamine deficiency in the pathogenesis of depression is considered. Poststroke depression is frequently diagnosed although it is detected using simple studies (Beck depression inventory, Hamilton rating scale). Psychotherapy is effective in preventing poststroke depression; the efficacy of antidepressants is actively being investigated. When depression develops, there is a positive result of treatment with antidepressants; a combination of psychotherapy and antidepressants produces even a more pronounced effect. The long-term (6-month or more) use of tricyclic antidepressants and selective serotonin reuptake inhibitors is noted to have a positive effect; there are data on the high efficacy and good tolerability of escitalopram in poststroke depression. It is stressed that the prevention and treatment of depression may substantially improve the rehabilitation process and quality of life.